2016
DOI: 10.3906/sag-1406-51
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related factors of psoriasis and seborrheic dermatitis: a community-based study

Abstract: In general, PS prevalence in this region was higher than in Asia and Africa but lower than in Europe and the United States. Whereas SD prevalence varies between 2% and 12% throughout the world, the average SD prevalence was 5.2% in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(67 reference statements)
0
10
1
1
Order By: Relevance
“…Seborrheic dermatitis was the most common dermatological finding in both PEXG and POAG patients. Several studies reported a prevalence of 1-15% for seborrheic dermatitis in the general population, [35][36][37] which is much lower than the observed frequency (57.1-61.5%) in our patients. This difference in prevalence can be either due to an association between the seborrheic dermatitis and glaucoma or the presence of dermatological issues due to lower hygiene and skincare in glaucoma patients.…”
Section: Discussioncontrasting
confidence: 80%
“…Seborrheic dermatitis was the most common dermatological finding in both PEXG and POAG patients. Several studies reported a prevalence of 1-15% for seborrheic dermatitis in the general population, [35][36][37] which is much lower than the observed frequency (57.1-61.5%) in our patients. This difference in prevalence can be either due to an association between the seborrheic dermatitis and glaucoma or the presence of dermatological issues due to lower hygiene and skincare in glaucoma patients.…”
Section: Discussioncontrasting
confidence: 80%
“…Possible causes of seborrhea -hereditary predisposition, the influence of external adverse factors, metabolic disorders and neuroendocrine disorders. The disease affects people of different ages and social status [2,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a slightly higher decrease in ASPR and ASIR in females between 2019 and 1990, while similar changes in ASDR were observed between both genders. Most studies found in the literature reported higher rates of prevalence and incidence in males than females [28][29][30][31][32][33][34], while other studies reported no differences between males and females [24,[35][36][37], and some described that females had higher incidence and prevalence [35,38,39]. The disparities in reported rates between males and females in various studies may be due to varying risk factors distributions between both groups [40], as well as the underrepresentation of female cases as mentioned previously, particularly in countries with lower SDI levels.…”
Section: Rates Differences By Gender and Agementioning
confidence: 99%